Violência de Gênero: uma análise sobre o feminicídio e o desenvolvimento econômico nas Unidades Federativas e Capitais no período de 2018-2021 - Lima, Natália Tamiris Sá de (Brasil, 2024)
In this study, the theoretical approach of the economics of crime was used to analyze gender violence, focusing on the analysis between the feminicide rate and socioeconomic indicators, such as the Human Development Index (HDI) of the Brazilian population during the period from 2018 to 2021. The methodology was carried out through an analysis of the Brazilian Public Security Forum database in relation to cases of feminicide, Atlas Brasil for IDH data and IBGE for demographic information about the states and capitals of Brazil. From the results, using the Spearman correlation test, it was possible to see that the HDI is not statistically significant in explaining the phenomenon of femicide. This raises questions about how the persistence of patriarchal family models may contribute to gender-based violence. Furthermore, the study highlighted the lack of effectiveness of services and trained professionals to address the problem of gender-based violence. Therefore, the results highlight the importance of investing in programs and public policies that guarantee the safety and protection of women.